Effect of defect states in the optical and magnetic properties of nanocrystalline NiO synthesised in a single step by an aerosol process. Issue 5 (1st April 2020) - Usharani, Nandhini J.; Bhattacharya, S.S.
Abstract: Nanocrystalline nickel oxide (NiO) was successfully synthesised as a phase-pure product from an inorganic precursor through a "single-pot", gas-phase synthesis method, nebulised spray pyrolysis (NSP). Functional properties such as magnetic behaviour, luminescence and band gap were studied and compared with the properties of NiO powder synthesised by a conventional reverse co-precipitation process (RCP) which also needed an additional calcination step. Although NiO crystallised in the cubic (rocksalt) form, Rietveld analysis of X-ray diffraction data revealed the synthesised nanopowders to be in a distorted cubic (rocksalt) or monoclinic form. This distortion resulted from the antiferromagnetic exchange interaction energy and increased magnetic surface anisotropy, as seen from the bond lengths determined from Fourier transform infra-red (FTIR) studies. Raman spectroscopy also confirmed the distortion in the structure indicated by the presence of a first order phonon peak. The band gap decreased in case of both the powders and was attributed to the shallow donor or acceptor levels created due to the presence of defect states as determined from photoluminescence studies. The NSP powders also exhibited a dependence on the excitation wavelength during emission luminescence. A mixed antiferromagnetic and ferromagnetic behaviour was observed in the NSP powders and the susceptibility of each was deconvoluted through low and high field magnetometry studies. Further, the nanopowders from both the processes showed "core-shell" magnetism, with paramagnetic behaviour in the shell and antiferromagnetism in the core. The thicknesses of the core and shell were also determined.